Double renal cell carcinoma with histological type of clear cell carcinoma and papillary carcinoma in the same kidney concurrently treated with robot‐assisted partial nephrectomy. Issue 1 (2nd December 2021) - Shimizu, Teruki; Hongo, Fumiya; Takahashi, Hikaru; Fujihara, Atsuko; Ukimura, Osamu
Abstract : Introduction: The presence of two different histologic types of renal cell carcinoma in the same kidney is rare in clinical practice. This report describes a patient with ipsilateral renal cell carcinomas, consisting of a clear cell renal cell carcinoma and a papillary type 1 renal cell carcinoma, who was successfully treated by robot‐assisted partial nephrectomy. Case presentation: A 70‐year man was referred to our hospital for the treatment of two right mid‐pole renal tumors, measuring 51 mm and 31 mm in diameter. The two tumors, which differed in contrast enhancement on computed tomography, were removed simultaneously by robot‐assisted partial nephrectomy. Histopathological and immunohistochemical findings confirmed that one tumor was a clear cell renal cell carcinoma, pT1a, and the other was a papillary type1 renal cell carcinoma, pT1b. Conclusion: This report describes a rare patient presenting with two ipsilateral renal cell carcinomas differing in histology. Robot‐assisted partial nephrectomy was the safe and effective nephron‐sparing surgery, even in patients with complex double renal tumors.